Reduction Of Malaysian Iron Ore Pellet By Using Coal As Reductant - Saidin, Hanizam Shah (2013)
Low grade iron ore sample obtained from Kuala Lipis, Pahang, Malaysia have been used throughout this study. Currently, the standard on carbothermal process that has been used by practitioners of the local industry is based on the international standard by external researchers using iron ore not from Malaysia. Therefore, the optimization of some significant parameters of Malaysian iron ore carbothermal process needs to be studied. With this regards, among the important variables including effects of temperature, carbon-iron oxide molar ratio, reduction time and amount of flux and binder on the reduction of iron oxide under nonisothermal and isothermal condition. For optimizations purposes, design of experiments (DOE) was utilized by applying the factorial design and response surface methodology. The iron ore sample was characterized by several methods including optical microscopy, XRF, SEM and XRD. XRF analysis indicated that the iron ore sample contained 81.2 wt. % of Fe2O3, 14.7 wt. % SiO2 and 3.5 wt. % Al2O3. XRD pattern confirmed that hematite and quartz were main phases present in the sample. The investigation showed that the compressive strength of roasted iron ore pellets decreased with the increasing of pellet basicity. Roasted pellets with calcium carbonate flux gave the highest compressive strength (7251 N/P), followed by barium carbonate (1410 N/P) and magnesium carbonate (39 N/P). Besides that, at room temperature, the thermal conductivity value for the pellet with magnesium carbonate flux gave the highest value (2.77 WmK-1) followed by pellet with calcium carbonate (2.48 WmK-1) and barium carbonate (2.25 WmK-1). Under nonisothermal conditions, the phase development of direct reduced iron ore samples has been analyzed. The mechanism of reduction was from Fe2O3  Fe3O4  FeO  Fe. From DOE analysis, temperature was the most influential parameter that showed strong interaction with the operating parameters (flux addition and time). The results of the analysis showed that the extent of reduction reached up to 99.9% at 1373 K with 5.0 wt.% flux. Under isothermal conditions, optimum results for carbon-iron oxide molar ratio (C/Fe2O3) were at 1:4.5. The analysis of reduction time showed that the sample took 60 minutes to achieve 92% reduction. Besides that, the optimum amount of flux to obtain a high reduction of 98.9% was 5.0 wt.%.